2023
DOI: 10.1007/s00520-023-07601-0
|View full text |Cite
|
Sign up to set email alerts
|

Barriers and facilitators to the engagement of physical activity among Black and African American cancer survivors during and after treatments

Abstract: Purpose To identify physical activity (PA) barriers and facilitators among Black and African American (Black/AA) cancer survivors that should be considered in future PA intervention development for this population. Methods A community advisory board (CAB) of Black/AA cancer survivors and patient advocates guided in-depth qualitative interviews ( n = 19) that were completed via telephone using a semi-structured interview guide. Interviews were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 31 publications
0
0
0
Order By: Relevance
“…. One step at a time Similar to Hirschey et al (26) participants in this study reported treatment related side effects (e.g., fatigue, pain), emotional wellbeing (". .…”
Section: The Journeysupporting
confidence: 65%
See 1 more Smart Citation
“…. One step at a time Similar to Hirschey et al (26) participants in this study reported treatment related side effects (e.g., fatigue, pain), emotional wellbeing (". .…”
Section: The Journeysupporting
confidence: 65%
“…Notably, compared to white CS, Black CS have been shown to be less likely to meet the recommended exercise guidelines (13). However, few studies have examined differences in CS physical activity and exercise behaviors by race/ethnicity (26) and none have explored this relationship in a Canadian context. Nova Scotia, a small province in Canada of ∼1 million people, is home to a unique population (2.3%) of peoples of African, Caribbean, and Black (ACB) descent, and is said to be the birthplace of Black culture in Canada (27-29).…”
Section: Introductionmentioning
confidence: 99%